Mg(2+) regulates transcription of mgtA in Salmonella Typhimurium via translation of proline codons during synthesis of the MgtL peptide - Gall, Aaron R. (Proc Natl Acad Sci U S A, 2016)
In Salmonella enterica serovar Typhimurium, Mg(2+) limitation induces transcription of the mgtA Mg(2+) transport gene, but the mechanism involved is unclear. The 5′ leader of the mgtA mRNA contains a 17-codon, proline-rich ORF, mgtL, whose translation regulates the transcription of mgtA [Park S-Y et al. (2010) Cell 142:737–748]. Rapid translation of mgtL promotes formation of a secondary structure in the mgtA mRNA that permits termination of transcription by the Rho protein upstream of mgtA, whereas slow or incomplete translation of mgtL generates a different structure that blocks termination. We identified the following mutations that conferred high-level transcription of mgtA at high [Mg(2+)]: (i) a base-pair change that introduced an additional proline codon into mgtL, generating three consecutive proline codons; (ii) lesions in rpmA and rpmE, which encode ribosomal proteins L27 and L31, respectively; (iii) deletion of efp, which encodes elongation factor EF-P that assists the translation of proline codons; and (iv) a heat-sensitive mutation in trmD, whose product catalyzes the m(1)G37 methylation of tRNA(Pro). Furthermore, substitution of three of the four proline codons in mgtL rendered mgtA uninducible. We hypothesize that the proline codons present an impediment to the translation of mgtL, which can be alleviated by high [Mg(2+)] exerted on component(s) of the translation machinery, such as EF-P, TrmD, or a ribosomal factor. Inadequate [Mg(2+)] precludes this alleviation, making mgtL translation inefficient and thereby permitting mgtA transcription. These findings are a significant step toward defining the target of Mg(2+) in the regulation of mgtA transcription.